Desiccation Mitigates Heat Stress in the Resurrection Fern, Pleopeltis polypodioides - John, Susan P.; Hasenstein, Karl H. (Frontiers in Plant Science, 2020)
Although heat and drought stresses often coincide, the response to heat especially in desiccation tolerant plants is rarely studied. We subjected hydrated Pleopeltis polypodioides fronds to temperatures up to 50 °C and dehydrated fronds up to 65 °C for 24 hrs. The effect of heat stress was evaluated using morphological changes, PS II efficiency and metabolic indicators. Pinnae of dried fronds exposed to more than 40 °C curled tighter and became brittle compared to fronds dried at lower temperatures. Exposure to > 50 °C lead to discolored fronds after rehydration. Hydrated fronds turned partially brown at > 35 °C. Chlorophyll fluorescence and quantum yield (Qy) increased following re-hydration but the recovery process after 40 °C treatment lasted longer than at lower temperatures. Similarly, hydrated fronds showed reduced Qy when exposed to > 40 °C. Dried and hydrated fronds remained metabolically active up to 40 °C. Hydroperoxides and lipid hydroperoxides in dried samples remained high up to 50 °C, but decreased in hydrated fronds at > 40 °C. Catalase and glutathione oxidizing activities remained high up to 40 °C in dehydrated fronds and up to 35 °C in hydrated fronds. Major fatty acids detected in both dehydrated and hydrated fronds included palmitic (C16:0) and stearic (C18:0) acids, oleic (18:1), linoleic (C18:2); and linolenic (C18:3) acids. Linolenic acid was most abundant. In dried fronds, all fatty acids decreased at > 35 °C. The combined data indicate that the thermotolerance of dry fronds is about 55 °C but is at least 10 °C lower for hydrated fronds.